Spread of the mcr-1 colistin-resistance gene in Escherichia coli through plasmid transmission and chromosomal transposition in French goats - Treilles, Michaël; Châtre, Pierre; Drapeau, Antoine; Madec, Jean-Yves; Haenni, Marisa (Frontiers in Microbiology, 2023)
Colistin-resistance widely disseminated in food-producing animals due to decades of use of colistin to treat diarrhea. The plasmid-borne mcr-1 gene has been extensively reported from bovine, swine and chicken worldwide, but smaller productions such as the goat farming sector were much less surveyed. In this study, we looked for colistin-resistant isolates presenting plasmid-borne genes of the mcr family in both breeding (n=80) and fattening farms (n=5). Only the mcr-1 gene was identified, in 10% (8/80) of the breeding farms and four over the five fattening farms. In total, 4.2% (65/1561) of the animals tested in breeding farms and 60.0% (84/140) of those tested in fattening farms presented an mcr-1-positive E. coli. Southern blot analysis coupled to short-read and long-read sequencing revealed that the mcr-1 gene was located either on the chromosome (32.2%) or on IncX4 (38.9%) and IncHI2 (26.8%) plasmids. As expected, both clonal expansion and plasmidic transfers were observed in farms where the mcr-1 gene was carried by plasmids. More interestingly, Tn6330 transposition was observed in diverse E. coli sequence types within the same farm, highlighting the fact that chromosomal insertion does not impair the transmission capability of the mcr-1 gene. Only strict hygiene and biosecurity procedures in breeding farms, as well as a prudent use of antibiotics in fattening farms, can avoid such complex contamination pathways.